White carbon black with high oil absorption value and preparation method thereof
High-purity white carbon black was prepared by precipitation method and materials such as nano zinc oxide were added to solve the problem of insufficient oil absorption of white carbon black, achieving high oil absorption and low-cost production, and meeting market demand.
Patent Information
- Application Number
- CN202510093569.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing white carbon black has weak oil absorption and is difficult to meet the market demand for highly oil absorption materials.
High-purity white carbon black was prepared by precipitation method, and nano zinc oxide, anti-aging agent and silane coupling agent were added during the preparation process, and the oil absorption of white carbon black was improved by mixing and dispersing treatment.
The high oil absorption of white carbon black is achieved, the production cost is reduced, the production process is simplified, and the market demand for highly oil absorption materials is met.
Smart Images

Figure BDA0005252253940000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of white carbon black preparation, in particular to white carbon black with high oil absorption value and a preparation method thereof. Background Art
[0002] White carbon black is a general term for white powdered X-ray amorphous silicic acid and silicate products, mainly referring to precipitated silica, fumed silica, ultrafine silica gel and aerogel, and also including powdered synthetic aluminum silicate and calcium silicate. White carbon black is a porous substance, and its composition can be expressed by SiO2·nH20, where nH20 exists in the form of surface hydroxyl groups. White carbon black is soluble in caustic alkali and hydrofluoric acid, insoluble in water, solvents and acids other than hydrofluoric acid, and has high temperature resistance, non-flammable, tasteless, odorless, and good electrical insulation. White carbon black is an environmentally friendly and excellent performance additive.
[0003] At present, the gas phase method is used to prepare white carbon black. However, the raw materials required for the white carbon black produced by the gas phase method are relatively expensive, and the steps are cumbersome. The present invention uses a precipitation method to prepare white carbon black. The raw materials used in the precipitation method to prepare white carbon black (such as sodium silicate, sulfuric acid or sulfuric acid, etc.) are relatively cheap, and the production process is relatively simple, so the cost is low. In addition, the precipitation method can produce white carbon black on a large scale to meet market demand. However, the oil absorption value of existing white carbon black is above 2.5, and the oil absorption of white carbon black is relatively weak. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a white carbon black with a high oil absorption value and a preparation method thereof, so as to solve the problem that the existing white carbon black has a low oil absorption.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: a high oil absorption value white carbon black and a preparation method thereof, comprising the method of preparing pure white carbon black by precipitation method;
[0008] A. The operation steps of preparing white carbon black are as follows:
[0009] Step 1: Prepare raw materials and mix:
[0010] 5-8 parts of sulfuric acid, 3-7 parts of water, 2-4 parts of quartz sand and 5-7 parts of soda ash. Mix quartz sand and soda ash in a ratio of 1:1.
[0011] Step 2, high temperature hydrolysis:
[0012] Add the mixed raw materials in step 1 into the reactor, perform a hydrolysis reaction at high temperature to obtain industrial water glass, and mix the industrial water glass with water in a ratio of 1:3 to obtain a dilute solution as a basic solution;
[0013] Step 3, precipitation reaction:
[0014] The dilute solution in step 2 is precipitated, sulfuric acid is added to the dilute solution to obtain SiO2, the pH value is 12-17, the dilution time is 1-2h, and the temperature is 73-77°C;
[0015] Step 4, filtration and washing:
[0016] The precipitate generated in step 3 (i.e., the initial form of white carbon black) is separated from the reaction solution by filtration, and then repeatedly washed with clean water;
[0017] Step 5: Deacidification treatment:
[0018] The particles in step 3 are placed in a plate-and-frame water washing system for deacidification, and sulfuric acid acid substances are removed by cleaning and filtering;
[0019] Step 6, drying and crushing;
[0020] After the deacidification treatment in step 5, a drying treatment is performed to remove moisture to obtain pure white carbon black, and then the white carbon black is pulverized;
[0021] B. The steps to improve the oil absorption of white carbon black are as follows:
[0022] Step 1: Prepare the ingredients:
[0023] 1-5 parts of nano zinc oxide, 3 parts of white carbon black, 4-7 parts of antioxidant and 6-9 parts of silane coupling agent;
[0024] Step 2: Mixing and dispersion:
[0025] Add the antioxidant and white carbon black in a mixing box at a ratio of 1:2 and mix them. During the mixing process, add a silane coupling agent to disperse the white carbon black.
[0026] Step 3: Add nano zinc oxide:
[0027] Add nano zinc oxide to the mixed raw materials in step 2, and use a grinding roller to disperse the nano zinc oxide so that the nano zinc oxide and the raw materials in step 2 are fully mixed to obtain white carbon black with high oil absorption.
[0028] Preferably, in step 2 of A, high temperature hydrolysis utilizes coal tar to heat quartz sand and soda ash for hydrolysis reaction at a temperature of 1400° C., and a stirring rod is used for mixing.
[0029] Preferably, in step 4 in A, filtering is performed using a plate and frame filter press, and washing is performed using a membrane filter press.
[0030] Preferably, in step 5 of A, a stirring rod is used for slow stirring to remove the acidic substance, and the acidic substance removed is sulfuric acid.
[0031] Preferably, the grinding in step 3 in B is performed using a grinding roller so that the nano zinc oxide dispersion can be mixed with the antioxidant and the white carbon black mixture.
[0032] (III) Beneficial effects
[0033] The present invention provides a high oil absorption value white carbon black and a preparation method thereof. It has the following beneficial effects:
[0034] The present invention utilizes a precipitation method to prepare high-purity white carbon black, and the raw materials used to prepare the white carbon black are relatively cheap, and the production process is relatively simple, so the cost is low, and nano zinc oxide is dispersed in the high-purity white carbon black and mixed with the white carbon black, and the oil absorption of the white carbon black can be improved after mixing. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] The embodiment of the present invention provides a high oil absorption value white carbon black and a preparation method thereof, including the method of preparing pure white carbon black by a precipitation method;
[0038] A. The operation steps of preparing white carbon black are as follows:
[0039] Step 1: Prepare raw materials and mix:
[0040] 5 parts of sulfuric acid, 3 parts of water, 2 parts of quartz sand and 5 parts of soda ash. Mix quartz sand and soda ash in a ratio of 1:1.
[0041] Step 2, high temperature hydrolysis:
[0042] Add the mixed raw materials in step 1 into a reactor, perform a hydrolysis reaction at high temperature, heat the reactor with coal tar, increase the temperature of the reactor, and perform a hydrolysis reaction to obtain industrial water glass, and mix the industrial water glass with water in a ratio of 1:3 to obtain a dilute solution as a basic solution;
[0043] Step 3, precipitation reaction:
[0044] The dilute solution in step 2 is precipitated, sulfuric acid is added to the dilute solution to obtain SiO2, and SiO2 is precipitated, the pH value is 12-17, the dilution time is 1-2h, the temperature is 73-77℃, water glass and sulfuric acid react to form hydrated sodium silicate, the chemical formula is: Na2OmS i O2+H2SO4+nH2O--→Na2SO4+mS i O2(n+1)H2O↓;
[0045] Step 4, filtration and washing:
[0046] The precipitate generated in step 3 (i.e., the initial form of white carbon black) is separated from the reaction solution by filtering to remove the residues and impurities in the solution, and then repeatedly washed with clean water to remove the impurities and excess solvent attached to the surface of the precipitate;
[0047] Step 5: Deacidification treatment:
[0048] The particles in step 3 are placed in a plate-and-frame water washing system for deacidification, and sulfuric acid acid substances are removed by cleaning and filtering;
[0049] Step 6, drying and crushing;
[0050] After the deacidification treatment in step 5, a drying treatment is performed to remove moisture, and a qualified white carbon black slurry is obtained by beating, and then the white carbon black slurry is sent to a drying tower for spray drying to obtain a white carbon black product, and pure white carbon black is obtained, and then the white carbon black is pulverized;
[0051] B. The steps to improve the oil absorption of white carbon black are as follows:
[0052] Step 1: Prepare the ingredients:
[0053] 1 part of nano zinc oxide, 3 parts of white carbon black, 4 parts of antioxidant and 6 parts of silane coupling agent;
[0054] Step 2: Mixing and dispersion:
[0055] Add the antioxidant and white carbon black in a mixing box at a ratio of 1:2 and mix them. During the mixing process, add a silane coupling agent to disperse the white carbon black.
[0056] Step 3: Add nano zinc oxide:
[0057] Add nano zinc oxide to the mixed raw materials in step 2, and use a grinding roller to disperse the nano zinc oxide so that the nano zinc oxide and the raw materials in step 2 are fully mixed to obtain white carbon black with high oil absorption.
[0058] In step 2 of A, high temperature hydrolysis utilizes coal tar to heat quartz sand and soda ash for hydrolysis reaction at a temperature of 1400°C, and a stirring rod is used for mixing. In step 4 of A, filtering is performed using a plate and frame filter press, and washing is performed using a diaphragm filter press. In step 5 of A, a stirring rod is used for slow stirring to remove acidic substances, and the removed acidic substance is sulfuric acid. In step 3 of B, grinding is performed using a grinding roller to allow the nano zinc oxide dispersion to be mixed with the antioxidant and the white carbon black mixture.
[0059] Embodiment 2:
[0060] The method comprises preparing pure white carbon black by precipitation method;
[0061] A. The operation steps of preparing white carbon black are as follows:
[0062] Step 1: Prepare raw materials and mix:
[0063] 6 parts of sulfuric acid, 5 parts of water, 3 parts of quartz sand and 6 parts of soda ash. Mix quartz sand and soda ash in a ratio of 1:1.
[0064] Step 2, high temperature hydrolysis:
[0065] Add the mixed raw materials in step 1 into a reactor, perform a hydrolysis reaction at high temperature, heat the reactor with coal tar, increase the temperature of the reactor, and perform a hydrolysis reaction to obtain industrial water glass, and mix the industrial water glass with water in a ratio of 1:3 to obtain a dilute solution as a basic solution;
[0066] Step 3, precipitation reaction:
[0067] The dilute solution in step 2 is precipitated, sulfuric acid is added to the dilute solution to obtain SiO2, and SiO2 is precipitated, the pH value is 12-17, the dilution time is 1-2h, the temperature is 73-77℃, water glass and sulfuric acid react to form hydrated sodium silicate, the chemical formula is: Na2OmS i O2+H2SO4+nH2O--→Na2SO4+mS i O2(n+1)H2O↓;
[0068] Step 4, filtration and washing:
[0069] The precipitate generated in step 3 (i.e., the initial form of white carbon black) is separated from the reaction solution by filtering to remove the residues and impurities in the solution, and then repeatedly washed with clean water to remove the impurities and excess solvent attached to the surface of the precipitate;
[0070] Step 5: Deacidification treatment:
[0071] The particles in step 3 are placed in a plate-and-frame water washing system for deacidification, and sulfuric acid acid substances are removed by cleaning and filtering;
[0072] Step 6, drying and crushing;
[0073] After the deacidification treatment in step 5, a drying treatment is performed to remove moisture, and a qualified white carbon black slurry is obtained by beating, and then the white carbon black slurry is sent to a drying tower for spray drying to obtain a white carbon black product, and pure white carbon black is obtained, and then the white carbon black is pulverized;
[0074] B. The steps to improve the oil absorption of white carbon black are as follows:
[0075] Step 1: Prepare the ingredients:
[0076] 3 parts of nano zinc oxide, 3 parts of white carbon black, 5 parts of antioxidant and 7 parts of silane coupling agent;
[0077] Step 2: Mixing and dispersion:
[0078] Add the antioxidant and white carbon black in a mixing box at a ratio of 1:2 and mix them. During the mixing process, add a silane coupling agent to disperse the white carbon black.
[0079] Step 3: Add nano zinc oxide:
[0080] Add nano zinc oxide to the mixed raw materials in step 2, and use a grinding roller to disperse the nano zinc oxide so that the nano zinc oxide and the raw materials in step 2 are fully mixed to obtain white carbon black with high oil absorption.
[0081] Embodiment three:
[0082] The method comprises preparing pure white carbon black by precipitation method;
[0083] A. The operation steps of preparing white carbon black are as follows:
[0084] Step 1: Prepare raw materials and mix:
[0085] 8 parts of sulfuric acid, 7 parts of water, 4 parts of quartz sand and 7 parts of soda ash. Mix quartz sand and soda ash in a ratio of 1:1.
[0086] Step 2, high temperature hydrolysis:
[0087] Add the mixed raw materials in step 1 into a reactor, perform a hydrolysis reaction at high temperature, heat the reactor with coal tar, increase the temperature of the reactor, and perform a hydrolysis reaction to obtain industrial water glass, and mix the industrial water glass with water in a ratio of 1:3 to obtain a dilute solution as a basic solution;
[0088] Step 3, precipitation reaction:
[0089] The dilute solution in step 2 is precipitated, sulfuric acid is added to the dilute solution to obtain SiO2, and SiO2 is precipitated, the pH value is 12-17, the dilution time is 1-2h, the temperature is 73-77℃, water glass and sulfuric acid react to form hydrated sodium silicate, the chemical formula is: Na2OmS i O2+H2SO4+nH2O--→Na2SO4+mS i O2(n+1)H2O↓;
[0090] Step 4, filtration and washing:
[0091] The precipitate generated in step 3 (i.e., the initial form of white carbon black) is separated from the reaction solution by filtering to remove the residues and impurities in the solution, and then repeatedly washed with clean water to remove the impurities and excess solvent attached to the surface of the precipitate;
[0092] Step 5: Deacidification treatment:
[0093] The particles in step 3 are placed in a plate-and-frame water washing system for deacidification, and sulfuric acid acid substances are removed by cleaning and filtering;
[0094] Step 6, drying and crushing;
[0095] After the deacidification treatment in step 5, a drying treatment is performed to remove moisture, and a qualified white carbon black slurry is obtained by beating, and then the white carbon black slurry is sent to a drying tower for spray drying to obtain a white carbon black product, and pure white carbon black is obtained, and then the white carbon black is pulverized;
[0096] B. The steps to improve the oil absorption of white carbon black are as follows:
[0097] Step 1: Prepare the ingredients:
[0098] 5 parts of nano zinc oxide, 3 parts of white carbon black, 7 parts of antioxidant and 9 parts of silane coupling agent;
[0099] Step 2: Mixing and dispersion:
[0100] Add the antioxidant and white carbon black in a mixing box at a ratio of 1:2 and mix them. During the mixing process, add a silane coupling agent to disperse the white carbon black.
[0101] Step 3: Add nano zinc oxide:
[0102] Add nano zinc oxide to the mixed raw materials in step 2, and use a grinding roller to disperse the nano zinc oxide so that the nano zinc oxide and the raw materials in step 2 are fully mixed to obtain white carbon black with high oil absorption.
[0103]
[0104] In summary, by comparing the above-mentioned Example 1, Example 2 and Example 3, the more nano zinc oxide is added, the higher the oil absorption of white carbon black is. Therefore, nano zinc oxide can effectively improve the oil absorption of white carbon black.
[0105] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high oil absorption value white carbon black and a preparation method thereof, characterized in that: The method comprises preparing pure white carbon black by precipitation method; A. The operation steps of preparing white carbon black are as follows: Step 1: Prepare raw materials and mix: 5-8 parts of sulfuric acid, 3-7 parts of water, 2-4 parts of quartz sand and 5-7 parts of soda ash. Mix quartz sand and soda ash in a ratio of 1:
1. Step 2, high temperature hydrolysis: Add the mixed raw materials in step 1 into the reactor, perform hydrolysis reaction at high temperature to obtain industrial water glass, and mix the industrial water glass with water in a ratio of 1:3 to obtain a dilute solution as a basic solution; Step 3, precipitation reaction: The dilute solution in step 2 is precipitated, sulfuric acid is added to the dilute solution to obtain SiO2, the pH value is 12-17, the dilution time is 1-2h, and the temperature is 73-77°C; Step 4, filtration and washing: The precipitate generated in step 3 (i.e., the initial form of white carbon black) is separated from the reaction solution by filtration, and then repeatedly washed with clean water; Step 5: Deacidification treatment: The particles in step 3 are placed in a plate-and-frame water washing system for deacidification, and sulfuric acid acid substances are removed by cleaning and filtering; Step 6, drying and crushing; After the deacidification treatment in step 5, a drying treatment is performed to remove moisture to obtain pure white carbon black, and then the white carbon black is crushed to finally obtain high-purity white carbon black; B. The steps to improve the oil absorption of white carbon black are as follows: Step 1: Prepare the raw materials: 1-5 parts of nano zinc oxide, 3 parts of white carbon black, 4-7 parts of antioxidant and 6-9 parts of silane coupling agent; Step 2: Mixing and dispersion: Add the antioxidant and white carbon black in a mixing box at a ratio of 1:2 and mix them. During the mixing process, add a silane coupling agent to disperse the white carbon black. Step 3: Add nano zinc oxide: Add nano zinc oxide to the raw materials mixed in step 2, and use a grinding roller to disperse the nano zinc oxide so that the nano zinc oxide and the raw materials in step 2 are fully mixed to obtain white carbon black with high oil absorption.
2. The high oil absorption white carbon black according to claim 1, characterized in that: In step 2 of A, high temperature hydrolysis utilizes coal tar to heat quartz sand and soda ash for hydrolysis reaction at a temperature of 1400° C., and a stirring rod is used for mixing.
3. The high oil absorption white carbon black according to claim 1, characterized in that: In step 4 of A, filtering is performed using a plate and frame filter press, and washing is performed using a membrane filter press.
4. The high oil absorption white carbon black according to claim 1, characterized in that: Step 5 in A is characterized in that the stirring rod is used for slowly stirring to remove the acidic substance, and the acidic substance removed is sulfuric acid.
5. The high oil absorption white carbon black according to claim 1, characterized in that: In step 3 of said B, grinding is performed by using a grinding roller so that the nano zinc oxide is dispersed and can be mixed with the antioxidant and the white carbon black mixture.